ANALISIS SENTIMEN ULASAN GAME HARRY POTTER: HOGWARTS MYSTERY PADA SITUS GOOGLE PLAY MENGGUNAKAN NAÏVE BAYES CLASSIFIER - Puti Ayu Andhini Rahman (2021)
One of the impacts of Covid-19 pandemic is everyone must be at home to minimize the spread of the virus and they feel bored because recreational park or play places are closed, to eliminate this feeling of saturation, many of them are looking for entertainment through video games both online and offline. Harry Potter: Hogwarts Mystery is an online role-playing video game set in the Harry Potter story based on the JK Rowling novel series. This game is included in the editor's choice on the Google Play Store, developed by Jam City with a license from Portkey Games, which was released on April 25th, 2018 for Android and iOS devices. In developing this game, of course, user reviews are one of the many important things for developers to consider. User reviews stored in the Google Play Store database can be used as research material for user analysis. Reviews from game users containing positive impressions or negative criticism, which certainly affects the rating of game, in order that the game can continue to develop. To monitor these reviews, a method is needed that can outline user sentiment, the method used in this study involves data collection activities using a web scraper, through data preprocessing, word weighting, and techniques used for sentiment classification using Naïve Bayes. A classifier that can categorize user reviews without having to do it manually. The purpose of this study is to classify these reviews and obtain useful information for interested parties. The results of the classification are expected to be able to categorize the sentiment groups of Harry Potter: Hogwarts Mystery users with a fairly high level of accuracy.